Morrey Meets Herz with Variable Exponent and Applications to Commutators of Homogeneous Fractional Integrals with Rough Kernels. (25th September 2017) - Wang, Hongbin; Wang, Jiajia; Fu, Zunwei
Abstract : We define the new central Morrey space with variable exponent and investigate its relation to the Morrey-Herz spaces with variable exponent. As applications, we obtain the boundedness of the homogeneous fractional integral operator T Ω, σ and its commutator [ b, T Ω, σ ] on Morrey-Herz space with variable exponent, where Ω ∈ L s ( S n - 1 ) for s ≥ 1 is a homogeneous function of degree zero, 0 < σ < n, and b is a BMO function.